HDAC1 regulates inflammation and osteogenic differentiation of ankylosing spondylitis fibroblasts through the Wnt-Smad signaling pathway - Yong Zeng; Rui He; Yong Liu; Ting Luo; Qing Li; Yu He; Miao Fang; Taiping Wang (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Ankylosing spondylitis (AS) is a refractory autoimmune disease, whose typical pathology is the development of inflammation to ossification and ankylosis. Histone deacetylase 1 (HDAC1) is considered to be a key factor involved in inflammatory gene transduction, but its role in AS remains unclear. The purpose of this study was to explore the role and possible mechanism of HDAC1 in AS based on the Wnt-Smad pathway. Fibroblasts were isolated from hip synovial tissues of AS patients, adeno-associated virus (AAV) was used to regulate the expression of HDAC1, DKK-1 and SIS3 was used to inhibit Wnt and Smad, respectively. The expressions of Wnt-Smad pathway-related proteins were analyzed by WB, and the TRP ion channel proteins were analyzed by immunofluorescence and WB. The proliferation of AS fibroblasts was detected by CCK-8, the expression of inflammatory cytokines was detected by ELISA, and the effects of HDAC1 on osteogenic differentiation of AS fibroblasts were investigated by alkaline phosphatase (ALP) activity, intracellular calcium concentration, mineralization and osteogenic proteins expressions. Results showed that HDAC1 significantly affected the protein expressions of the Wnt-Smad pathway in AS fibroblasts, and Wnt inhibitor DKK-1 and Smad3 inhibitor SIS3 could significantly reverse the effect of HDAC1 on the Wnt-Smad pathway. In addition, HDAC1 significantly activated the TRP ion channel and promoted the proliferation, inflammatory response and osteogenic differentiation of AS fibroblasts. DKK-1 or SIS3 treatment significantly inhibit the effect of HDAC-1 on AS fibroblasts, suggesting that the Wnt-Smad pathway is involved in the regulation of AS by HDAC1. In conclusion, HDAC1 promotes the proliferation, inflammatory response and osteogenic differentiation of AS fibroblasts through the Wnt-Smad pathway.